Experience of Blended Learning in the Basics of Digital Electronics - M. S. Dolinsky (Цифровая трансформация)
The article considers the practical experience of blended learning of students in the basics of digital electronics based on the use of the instrumental distance learning system DL.GSU.BY developed at the FranciskSkorinaGomelStateUniversity. There are described specialized tools for designing, modeling, debugging, and researching digital electronics devices developed specifically for learning the basics of digital electronics.